1997
DOI: 10.1111/j.1745-4530.1997.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

INACTIVATION OF ESCHERICHIA COLI IN SKIM MILK BY HIGH INTENSITY PULSED ELECTRIC FIELDS

Abstract: The inactivation of microorganisms is the most important function in the processing of milk and dairy products. Traditionally, this purpose is realized by thermal treatment, but heat produces alterations to flavor and taste in addition to nutrient loss. The high intensity pulsed electric field (PEF) treatment should be a good alternative to heat because demonstrations have shown PEF can reduce the Escherichia coli survival fraction in aqueous solutions and model foods. In this study, PEF treatment was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(69 citation statements)
references
References 35 publications
7
61
1
Order By: Relevance
“…The critical field intensities which are evaluated for Hülsheger and Peleg models, ranged from 6.5712-1.4743 to 8.993-1.663 kV/cm respectively. The evaluated critical field intensity is different from the other reported studies (Hülsheger et al 1981;Martín et al 1997;Zhong et al 2005). The cause of disagreement can be the environmental conditions and treatment setup used in these studies.…”
Section: Resultscontrasting
confidence: 41%
“…The critical field intensities which are evaluated for Hülsheger and Peleg models, ranged from 6.5712-1.4743 to 8.993-1.663 kV/cm respectively. The evaluated critical field intensity is different from the other reported studies (Hülsheger et al 1981;Martín et al 1997;Zhong et al 2005). The cause of disagreement can be the environmental conditions and treatment setup used in these studies.…”
Section: Resultscontrasting
confidence: 41%
“…Most of the earlier studies with PEF treatment were using small static treatment chambers held between parallel plates (Grahl & Märkl, 1996;Hülsheger & Niemann, 1980;. Qin et al (1995a) showed a greater treatment uniformity in continuous flow systems than in static systems, which was confirmed in a study by Martín et al (1997) who found more inactivation within a continuous flow system with parallel plate chamber than in a static parallel system. Thereafter, especially in translation of the process to pilot and commercial scales, the preference has been to conduct kinetic studies in continuous flow mode (Sastry, 2016).…”
Section: Processing Parameterssupporting
confidence: 65%
“…These factors most likely influence the recovery of injured microbial cells and their subsequent growth following PEF exposure, since the presence of food components, such as fats and proteins , has reportedly had a preventive effect on microorganisms against PEF treatment (Ho et aI., 1995;Grahl and Markl, 1996;Martin et al, 1997).…”
Section: Media Factorsmentioning
confidence: 99%